The Stagnation of Brazil's Exports: A Comment - Lowinger, Thomas C. (Quarterly Journal of Economics, 1970)
Journal Article The Stagnation of Brazil's Exports: A Comment Get access Thomas C. Lowinger Thomas C. Lowinger Washington State University Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 84, Issue 4, November 1970, Pages 699–704, https://doi.org/10.2307/1880853 Published: 01 November 1970